Spatio‐temporal variability in contributions to low flows in the high Alpine Poschiavino catchment. Issue 26 (23rd November 2018) - Floriancic, Marius G.; van Meerveld, Ilja; Smoorenburg, Maarten; Margreth, Michael; Naef, Felix; Kirchner, James W.; Molnar, Peter
Abstract: In order to predict streamflow accurately during extended dry periods, we need to understand the spatial variability of low flows and the extent to which it is affected by the spatial organization and drainage of catchment subsurface storage areas. This is especially true in Alpine catchments with widely varying topography, lithology, sediment deposits, and soil properties. Field measurements in the Poschiavino catchment in southern Switzerland, during a winter recession period without recharge, provided a unique opportunity to demonstrate the connections between subsurface storage areas, low flows, and their variability. We measured discharge in four nested sub‐catchments during seven field campaigns in the winter of 2013–2014. We analysed stream water electrical conductivity (EC) and water chemistry to identify the areas contributing to low‐flow discharge and estimated their contributions. Sediment cover type and thickness were mapped using a recently developed tool for geomorphology‐based storage classification of mountainous terrain, to determine the physical properties of the subsurface storage areas contributing to low‐flow discharge. Recession analyses combined with water chemistry data allowed the detection of different drainage timescales and the estimation of storage potential of the unconsolidated (Quaternary) deposits. We found substantial spatial variation in storage depletion between the sub‐catchments, ranging from 54 mm to 200 mm for the four‐month monitoring period. Variability in low‐flow contributions from different catchments and different recession behavior could be related to the differences in the estimated storage potential. For some point sources, we could quantify the contributing area and thus quantify low flows at the hillslope scale. Overall, the low‐flow variability is mostly related to the fraction of precipitation that recharges subsurface storage areas and to the properties influencing their drainage. To capture these processes, we suggest low‐flow geomorphological mapping approaches that consider not only morphometric (shape of the landscape) and geologic (properties of the bedrock) controls but also the water storage potential of debris cover and weathered rock.